Schools as Value Communities in Shaping Students' Personalities and Culture - Taqiyya, Wafa; Sutama, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
The phenomenon of declining student character, such as increasing intolerant behavior, weak social responsibility, and the fading value of honesty in the school environment indicates a value crisis that requires a new approach to character education. Most previous research still focuses on instructional-based character education, without a holistic view of the school's function as a value community. This study aims to analyze the role of schools as value communities in shaping students' personalities and culture. This study uses a qualitative approach with library research methods. Relevant scientific sources are analyzed to identify the main dimensions of value communities and their contribution to student character formation. The results of the study indicate that schools that fulfill their role as value communities are able to create social systems that support the internalization of values such as honesty, responsibility, collaboration, tolerance, and respect for local culture. The process of value formation occurs through teacher role models, meaningful social interactions, and consistent school policies and culture. This research provides theoretical and practical contributions in expanding the paradigm of character education from a cognitive-formal approach to an ecological, contextual, and transformative approach through the formation of schools as value communities.